One nudge can be enough: reducing cigarette butt littering in public areas - Klunin, Artsiom (Central European Public Administration Review, 2024)
The purpose of this paper is to investigate how public administration can reduce cigarette butt littering in public areas. Cigarette butt littering is a problem for every local government unit; however, policy solutions are either very difficult to implement or expensive. This paper demonstrates the potential of behavioural science, namely nudges employing gamification, salience, and priming. Design/Methodology/Approach: In collaboration with local public administration, two field quasi-experiments were conducted to explore the effectiveness of low-complexity behavioural measures to tackle cigarette butt littering in heterogeneous public spaces. The study tested both the effectiveness of a single behavioural measure and the follow-up effect of a combination of low-complexity measures. In the first quasi-experiment, a standalone intervention (priming stickers) and the follow-up combination of measures (priming stickers with gamified ballot bins) were tested. In the second quasi-experiment, a standalone salience nudge (crime scene) was first implemented, followed by a combination of the initial (crime scene) and follow-up salience (toxicity) nudges to nudge smokers from cigarette butt littering in public space. Both quasi-experiments used a before-and-after design. Findings: The results suggest that a single behavioural intervention may be sufficient to achieve the desired behavioural change, and reinforcing its effects within a relatively short time period with a follow-up intervention may not deliver any additional statistically significant effects. Originality/Value: This research contributes to public administration research, specifically by applying behavioural insights and experimental approaches to studying public policies. Although this approach is gaining popularity, there remains a lack of evidence from field (quasi-)experimental studies on the effects of behavioural interventions in reducing pollution in public spaces.
Keywords: cigaretni ogorki; cigarette butts; gamification; igrifikacija; littering; namig; nudge; poudarjanje; priming; salience; smetenje; sugestija